Analisis Potensi Nilai Ekonomi Sampah dari Aktivitas Perkantoran di Kota Pontianak - Salsabila, Thalita Helga; Akbar, Aji Ali; Jati, Dian Rahayu (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
Offices are one source of waste from commercial areas that are required to implement waste management. Waste from offices is in the form of paper, plastic bottles, packaging boxes and so on which have economic value. This research aims to analyze the generation and composition of waste, the economic value of office waste, as well as the relationship between office waste generation and the economic value of waste from office activities in Pontianak City as a basis for efforts to reduce waste and develop a waste bank. Measurement of waste generation and composition from office activities is carried out in accordance with SNI 19-3964-1994 and then the economic value of waste is calculated based on the selling price of waste at the Waste Bank and TPS 3R Palem Asri. Statistical analysis is used to determine the relationship between office waste generation and the economic value of waste. The average waste generation from office activities in Pontianak City is 177.72 kg/day and the volume is 2,742.72 liters/day. The largest waste composition is other types of waste at 39.2% and the smallest is aluminum waste at 0.1%. The resulting economic value is IDR 137,778/day and IDR 50,288,840/year. The results of statistical tests using correlation analysis show that the correlation coefficient value is 0.961. It is concluded that the two variables tested have a very strong correlation and are positive or in the same direction so that the higher the generation of office waste, the greater the economic value of waste.